(untitled) (Dristikon: A Multidisciplinary Journal, 2020)
This paper aims at looking into varieties of the Mundhum language and reasons for its intricacies to the Limbu natives. The study attempts to follow the qualitative research design which involves collecting non-numerical data especially the religious text or discourse for analysis and interpretation. After the related data were collected, the linguistic theory specifically linguistic typology is used to analyze, compare and interpret them. The findings ofthis study indicated that the Mundhum or the religious scripture of the Limbu community does have a specific language variety which emerges out from the diglossic situation. According to the diglossic situation, the Mundhum serves as the high variety. This high variety is employed in formal social functions and ritual performances. To the contrary, the ordinary languagevariety of Limbu is used in every day communicative purposes and this type of speech variety is considered to be low variety in the sociolinguistics’ field. There are certain reasons which make it very complicated to the natives to comprehend the Mundhum. Inquisitive individual’s in the study of typological linguistics of the religious text are expected to get help from this study.